Mixed convection boundary layer flow over a horizontal circular cylinder in a Williamson hybrid ferrofluid with viscous dissipation effect - Marjan, Mohd Daud; Muhammad Khairul Anuar, Mohamed; Norhafizah, Md Sarif; Muhamed Abdul Fatah, Muhamed Mukhtar; Alkasasbeh, Hamzeh Taha (Semarak Ilmu Publishing, 2026)
This research paper focuses on the flow of Williamson hybrid ferrofluid on mixed convection boundary layer flow via a horizontal circular cylinder. The mathematical model discussed reflect to the investigation of flow characteristics and the heat transfer capabilities of a hybrid ferrofluid. The problem starts with a system of partial differential equations which govern the problem together with suitable initial and boundary conditions. In addition, this problem also considered the presence of magnetohydrodynamic (MHD) effect and viscous dissipation. The dimensional governing equations together with its initial and boundary conditions are converted into dimensionless governing equations by using the proper dimensionless variables. The Keller-box technique is used to solve the partial differential equation numerically where these equations are generated from the modification of the dimensionless governing equation and non-similarity transformation. Various pertinent parameters are acquired and discussed in this research. The results showed that the skin friction coefficient and Nusselt number have increased because of the ferrofluid’s increased nanoparticle volume. The Williamson hybrid ferrofluid performed better than Williamson ferrofluid in terms of heat transfer capacity with high friction between the fluid and the cylinder surface.